Quadrupole-Time-of-Flight Mass Spectrometric Identification of Hemoglobin Subunits α, β, γ and δ in Unknown Peaks of High Performance Liquid Chromatography of Hemoglobin in β-Thalassemias. (4th May 2019) - Abdullah, Uday Y.H.; Ibrahim, Hishamshah M.; Mahmud, Noraesah B.; Salleh, Mohamad Z.; Kek, Teh L.; Noorizhab, Mohd N.F.B.; Jassim, Haitham M.; Othman, Iekhsan; Zainal Abidin, Syafiq A.; Zilfalil, Bin Alwi; Wilairat, Prapin; Fucharoen, Suthat
Abstract: This is the first report of quadrupole time-of-flight (Q-TOF) mass spectrometric identification of the hemoglobin (Hb) subunits, α, β, δ and γ peptides, derived from enzymatic-digestion of proteins in the early unknown peaks of the cation exchange chromatography of Hb. The objectives were to identify the unknown high performance liquid chromatography (HPLC) peaks in healthy subjects and in patients with β-thalassemia (β-thal). The results demonstrate the existence of pools of free globin chains in red blood cells (RBCs). The α-, β-, δ- and γ-globin peptides were identified in the unknown HPLC peaks. The quantification and role of the free globin pool in patients with β-thal requires further investigation. Identification of all types of Hb subunits in the retention time (RT) before 1 min. suggests that altered Hbs is the nature of these fast-eluting peaks. Relevancy of thalassemias to the protein-aggregation disorders will require review of the role of free globin in the pathology of the disease.